2021
DOI: 10.3389/fevo.2021.618331
|View full text |Cite
|
Sign up to set email alerts
|

A Link Between Communities of Protective Endosymbionts and Parasitoids of the Pea Aphid Revealed in Unmanipulated Agricultural Systems

Abstract: In the last decade, the influence of microbial symbionts on ecological and physiological traits of their hosts has been increasingly recognized. However, most of these effects have been revealed under laboratory conditions, which oversimplifies the complexity of the factors involved in the dynamics of symbiotic associations in nature. The pea aphid, Acyrthosiphon pisum, forms a complex of plant-adapted biotypes, which strongly differ in the prevalence of their facultative endosymbionts. Some of the facultative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 57 publications
(105 reference statements)
1
27
1
Order By: Relevance
“…Beyond the use of bacterial genomes to help reconstruct aphid phylogeography, the composition of the bacterial populations in aphids might also help to assess the importance of facultative bacteria for colonizing new geographic regions. Many studies have investigated variation in bacterial communities associated with the pea aphid (Acyrthosiphon pisum Harris), revealing geographical variation, host-specific differentiation and associations with environmental factors such as temperature, host plants, and natural enemies (Tsuchida et al 2002;Russell et al 2013;Zepeda-Paulo et al 2018;Leclair et al 2021). The effect of endosymbionts on aphid fitness has been confirmed experimentally in certain cases (Leclair et al 2016;Frago et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the use of bacterial genomes to help reconstruct aphid phylogeography, the composition of the bacterial populations in aphids might also help to assess the importance of facultative bacteria for colonizing new geographic regions. Many studies have investigated variation in bacterial communities associated with the pea aphid (Acyrthosiphon pisum Harris), revealing geographical variation, host-specific differentiation and associations with environmental factors such as temperature, host plants, and natural enemies (Tsuchida et al 2002;Russell et al 2013;Zepeda-Paulo et al 2018;Leclair et al 2021). The effect of endosymbionts on aphid fitness has been confirmed experimentally in certain cases (Leclair et al 2016;Frago et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, asexual reproduction allows for a rapid increase in population size after the colonization of a favorable new environment (Simon et al 2002(Simon et al , 2010Figueroa et al 2018). So far, only a handful of studies have reconstructed the colonization history of aphid crop pests by combining population genetics approaches using the information from SSR, sequence or single nucleotide polymorphism (SNP) markers (Peccoud et al 2008;Zepeda-Paulo et al 2010;Piffaretti et al 2013;Zhang et al 2014;Zhou et al 2015;Kim et al 2016;Fang et al 2018;Morales-Hojas et al 2020;Giordano et al 2020;Leclair et al 2021). These studies demonstrated that aphid species can spread very quickly across the world, probably via plants transported by humans and/or wind.…”
Section: Introductionmentioning
confidence: 99%
“…the genus Rickettsia [20,21] and Wolbachia [22,23]] and Mollicutes of Spiroplasma genus [24,25]. Ecological effects associated with these bacterial partners include defense against parasites [26][27][28][29][30], body color modification [31,32], heat stress tolerance [33], host plant use and nutrition [34,35] and host reproductive manipulation [36].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, asexual reproduction allows for a rapid increase in population size after the colonization of a favorable new environment (Simon, Rispe, & Sunnucks, 2002; Simon, Stoeckel, & Tagu, 2010; Figueroa, Fuentes-Contreras, Molina-Montenegro, & Ramírez, 2018). So far, only a handful of studies have reconstructed the colonization history of aphid crop pests by combining population genetics approaches using the information from SSR, sequence or single nucleotide polymorphism (SNP) markers (Fang, Chen, Jiang, Qu, & Qiao, 2018; Giordano et al, 2020; Kim, Hoelmer, & Lee, 2016; Leclair, Buchard, Mahéo, Simon, & Outreman, 2021; Morales-Hojas, Sun, Iraizoz, Tan, & Chen, 2020; Peccoud et al, 2008; Piffaretti et al, 2013; Zepeda-Paulo et al, 2010; Zhang et al, 2014; Zhou et al, 2015). These studies demonstrated that aphid species can spread very quickly across the world, probably via plants transported by humans and/or wind.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the use of bacterial genomes to help reconstruct aphid phylogeography, the composition of the bacterial populations in aphids might also help to assess the importance of facultative bacteria for colonizing new geographic regions. Many studies have investigated the variation in bacterial communities associated with the pea aphid ( Acyrthosiphon pisum Harris), revealing geographical variation, host-specific differentiation and associations with environmental factors such as temperature, host plants, and natural enemies (Russell et al, 2013; Tsuchida, Koga, Shibao, Matsumoto, & Fukatsu, 2002; Zepeda-Paulo, Ortiz-Martínez, Silva, & Lavandero, 2018; Leclair et al, 2021). The effect of endosymbionts on aphid fitness has been confirmed experimentally in certain cases (Frago et al, 2017; Leclair et al, 2016).…”
Section: Introductionmentioning
confidence: 99%